PENERAPAN PENDIDIKAN KARAKTER DI HOMESCHOOLING MELALUI PEMBELAJARAN REFLEKTIF - Irfan Fatkhurrahman; Ahmad Zuber; Supriyadi Supriyadi; Afif Muchlisin (Jurnal Analisa Sosiologi, 2020)
This study aimed to analyze 1) Homeschooling as an Alternative to Non-Formal Education with the support of Paulo Freire’s educational theory for freedom, 2) The Implementation of Character Education through Reflective Learning at PKBM Homeschooling Primagama Solo. The study used qualitative research methods with case study strategy. The determination of informants used purposive sampling techniques. The informants consisted of one key informant, 4 main informants, and 7 supporting informants. The data collection was carried out using a participant observation technique in the field, in-depth interviews, and documentation studies. The data were analyzed in three stages, including data reduction, data display, and drawing conclusions. The data were verified by source triangulation. The results showed that 1) Primagama could be an alternative to non-formal education with the facilities and services provided. However, referring to Freire’s educational theory for freedom which revealed 4 important points: the relationship between teacher and student, educational methods, educational curriculum, and educational goals, it obtained that education in homeschooling had not been fully liberated because the curriculum was still followed the rules and due to problems of education costs which caused not all people could experience this type of education, 2) The implementation of the four levels of reflective learning hierarchy: habitual action, understanding, reflection, and critical reflection had an impact on the self-development and critical thinking of homeschooling students. The more students move to the right and have broader critical thinking in the continuum of the hierarchy, the learning outcomes in homeschooling are expected to be of higher quality. Keywords: Character Education, Freedom Education, Homeschooling, Reflective learning.  AbstrakPenelitian ini bertujuan untuk menganalisis 1) Homeschooling Sebagai Alternatif Pendidikan Nonformal dengan didukung teori pendidikan untuk pembebasan dari Paulo Freire, 2) Penerapan Pendidikan Karakter Melalui Pembelajaran Reflektif di PKBM Homeschooling Primagama Solo. Penelitian menggunakan metode penelitian kualitatif  dengan strategi studi kasus. Penentuan informan menggunakan teknik purposive sampling. Informan terdiri dari satu informan kunci, 4 informan utama, dan 7 informan pendukung. Pengumpulan data dilakukan dengan teknik observasi partisipan di lapangan, wawancara (in-depth interview), dan studi dokumentasi. Data dianalisis dalam tiga tahap yaitu reduksi data, penyajian data, dan diakhiri dengan penarikan kesimpulan. Data diverifikasi dengan triangulasi sumber. Hasil penelitian menunjukkan 1) Primagama bisa menjadi salah satu alternatif pendidikan nonformal dengan fasilitas dan pelayanan yang diberikan. Namun mengacu pada teori pendidikan untuk pembebasan dari Freire yang mengungkap 4 poin penting : hubungan guru dan murid, metode pendidikan, kurikulum pendidikan, dan tujuan pendidikan, ternyata ditemukan bahwa pendidikan dalam homeschooling belum sepenuhnya membebaskan dikarenakan kurikulum yang masih mengikuti aturan dan masalah biaya pendidikan sehingga tidak semua masyarakat bisa untuk menikmati pendidikan jenis ini, 2) Penerapan empat hierarki pembelajaran reflektif : tindakan rutin, pengertian, refleksi, dan refleksi kritis berdampak bagi pengembangan diri dan pemikiran kritis siswa homeschooling. Semakin siswa bergerak ke kanan dan mempunyai pemikiran kritis yang lebih luas dalam kontinum hierarki, maka hasil belajar dalam homeschooling diharapkan menjadi lebih bermutu.Kata kunci: Pendidikan karakter, Pendidikan Pembebasan, Homeschooling, Pembelajaran reflektif.